Multigenerational Exposure to Nano‐TiO2 Induces Ageing as a Stress Response Mitigated by Environmental Interactions. Issue 6 (8th April 2021) - Ellis, Laura-Jayne A.; Kissane, Stephen; Hoffman, Elijah; Valsami-Jones, Eugenia; Brown, James B.; Colbourne, John K.; Lynch, Iseult
Abstract : Despite their ubiquity in personal care products, the health implications of titanium dioxide (TiO2 ) nanomaterials (NMs) are under strenuous investigation for their potential as a carcinogen, whereas other evidence has shown links with premature ageing. Both potential hazards are manifested after chronic exposure. To explore the chronic effects of TiO2 NMs in the environment, a multigenerational study using the model test species Daphnia magna is conducted. Phenotypical characteristics associated with ageing are observed (loss or shortening of tails and lipid accumulation) with increased expression of highly conserved key stress response genes involved in inflammatory responses and oxidative stress. These responses are visible in continuously exposed daphnids over four generations and in daphnids removed from maternal exposure even three generations later. However, exposure to the "aged" variants of these NMs at the same concentrations significantly reduced these effects, and exposure in medium containing natural organic matter is less severe than in salt‐only medium. Abstract : Expression of highly conserved stress‐response genes and phenotypical changes associated with accelerated daphnid ageing are observed over multiple generations of Daphnia exposed to pristine nanomaterials (NMs). The toxic effects are dramatically reduced using environmentally transformed NMs that are "aged" in the test medium and/or through use of more realistic natural water compositions containing natural organic matter (NOM).